Essentials of ADHD assessment for children and adolescents - Sparrow, Elizabeth P.; Erhardt, Drew. (U.S.A. : John Wiley & Sons, Inc., 2014)
"This indispensable resource provides step-by-step guidelines for conducting a thorough, responsible evaluation for ADHD in children and adolescents. Focusing on the pragmatic needs of the practicing clinician, the authors address not only the broad concepts integral to conducting sound ADHD assessments but also the specifics that will enable practitioners to implement those principles. This essential guide is appropriate for seasoned clinicians who wish to add ADHD evaluations to their practices, as well as new clinicians and graduate students who are developing expertise. "--
Machine generated contents note: Foreword Series Preface Preface Acknowledgements Chapter 1 Understanding ADHD Chapter 2 What the DSM-5 says about ADHD Chapter 3 Assessing ADHD: Goals & Guiding Principles Chapter 4 Components of ADHD Assessment Chapter 5 Putting it All Together: Integrating Findings & Drawing Conclusions Chapter 6 Illustrative Case Reports Annotated Bibliography About the Authors.
Includes bibliographical references and index.
Keywords: Attention-deficit-disordered children; Attention-deficit disorder in adolescence; Attention-deficit-disordered children -- Psychological testing; Attention-deficit disorder in adolescence -- Diagnosis; PSYCHOLOGY / Clinical Psychology